Automated 3D reconstruction of Lodox Statscan images for forensic application - Bolton, Frank (Division of Biomedical Engineering, 2014)
The main objectives of this project are to perform tomographic reconstruction with manually scanned projection data from a Lodox Statscan full body digital radiography system, and to produce tools to allow automated generation of information required to perform the tomographic reconstruction.